HUBUNGAN DIMENSI KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN RAWAT INAP PADA RSUP DR TADJUDDIN CHALID MAKASSAR - Nurhasma Nurhasma; Andi Syamsul Rijal; Rahmawati Azis (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
Quality in a Hospital Service is closely related to Inpatient Patient Satisfaction in Hospitals in Indonesia. Patient satisfaction is one of the important indicators to control the quality of health services in hospitals. The results of the study indicate that the level of patient satisfaction in several hospitals in Indonesia is still below the standard set by the government (>90%). The purpose of this study was to determine the relationship between the dimensions of the quality of health services with the satisfaction of inpatients at the hospital. Data analysis used univariate, bivariate (Chi-Square test) and multivariate (Logistic Regression test) analysis. The results showed that the level of patient satisfaction was 96.6%, this means that the satisfaction level of inpatients in hospitals in Indonesia is good because it meets the customer satisfaction standards set by the Indonesian Ministry of Health (>90%). Multivariate analysis showed a significant relationship between, service, environment and hospital facilities. The results of this study can be concluded that the quality of health services received by atients is very influential on patient satisfaction itself